IMPLEMENTATION OF E-FLIPBOOK LEARNING MEDIA ON NATURAL AND SOCIAL SCIENCES’ LEARNING OUTCOMES AT FOURTH-GRADE ELEMENTARY STUDENTS - Restu Nurhamidah; Nurlinda Safitri; Maulida Intan Akmala (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the implementation of E-Flip Book learning media through the Problem-Based Learning model on learning outcomes of Natural and Social Sciences (IPAS) for fourth-grade elementary students. The research was conducted on 24 fourth-grade students at SD Negeri Bantarjati 9 North Bogor in Bogor in the odd semester of the Academic Year 2022/2023. The research design was Classroom Action Research (PTK), which was carried out through four stages; planning, implementing, observing, and reflecting. The research consisted of the first cycle and second cycle. Data analysis techniques used descriptive statistical analysis to describe data that are related to the teacher’s and students’ activity observation. The research results indicate in the pre-cycle students who achieved complete criteria were 14% and those who did not complete were 86%. In addition, in cycle I it implies that students who obtained complete criteria were 45% and those who did not complete were 55%. In cycle II, the students who achieved the criteria of completion were 88% and those who did not complete were 13%. Thus, the implementation of the E-Flip Book learning media through the Problem-Based Learning model reveals a significant improvement and success to increase students’ learning outcomes at a percentage of 74%.